Cellular Response of the Rabbit Eye to Primary Intravitreal Injection of Neisseria meningitidis - Pribnow, James F. (1971)
New Zealand White rabbits were injected intravitreally with approximately 2,500 viable or heat-killed meningococci. The rabbits were killed at intervals from 30 min to 14 days after injection. None of the rabbits produced detectable antibodies. Local antibody production by uveal tract, spleen, or preauricular lymph node cells was not demonstrated. Viable organisms were recovered from the vitreous at periods from 30 min to 48 hr after injection. Failure to recover viable organisms could be correlated with the appearance of large numbers of polymorphonuclear neutrophiles (PMN) throughout the vitreous. Animals injected with viable meningococci demonstrated a progressive inflammatory reaction characterized by an early accumulation of PMN in the vitreous, limbus, and conjunctiva. The cellular infiltrate gradually became mononuclear. By the 14th day postinjection only a few residual inflammatory cells remained at the limbus. This extensive cellular response was lacking in recipients of heat-killed organisms. The defense of the rabbit against intraocular introduction of meningococci therefore seems to be predominantly a cellular mechanism.